2009
DOI: 10.1021/jp810811b
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Investigation of Methanol Dehydrogenation on Pd(111)

Abstract: Methanol dehydrogenation to CO and H on Pd(111) is systematically investigated using self-consistent periodic density functional theory (DFT). All possible intermediates involved are calculated. Methanol and formaldehyde adsorb weakly on the Pd(111) surface because they are saturated molecules. CO and H prefer 3-fold sites with the adsorption energies of 41.6 and 64.4 kcal/mol. CH 3 O binds stably at 3-fold and bridge sites. Most of the other intermediates are inclined to adsorb to the surface with the sp 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
177
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(221 citation statements)
references
References 84 publications
42
177
2
Order By: Relevance
“…7. A similar bonding geometry has been found in previous DFT calculations of methanol adsorption on Pd(111) [28,74,75], Ag(110) [76], and Ag(111) [77]. …”
Section: Methanol Adsorption and Decomposition On Ag/pd(110)supporting
confidence: 84%
“…7. A similar bonding geometry has been found in previous DFT calculations of methanol adsorption on Pd(111) [28,74,75], Ag(110) [76], and Ag(111) [77]. …”
Section: Methanol Adsorption and Decomposition On Ag/pd(110)supporting
confidence: 84%
“…The adsorption energy of H at the Fcc site is calculated to be -2.83 eV, which is 0.04 eV more negative that than at the Hcp site. In the most stable adsorption configuration, the H atom is exactly centered over the Fcc site with three equal H-Pd distances of 0.182 nm, which agrees well with the previous calculations [14,16].…”
supporting
confidence: 91%
“…Previous slab model calculations indicated that CH 3 O preferred the three-fold fcc hollow site and the bridge site on pure Pt(111) [27] and pure Pd(111) [53], whereas the top site was not stable. However, the top, bridge, hcp and fcc sites were all found in this study, among which the fcc and hcp adsorptions were similar, and CeO bond was almost perpendicular to the surface.…”
Section: Methoxy (Ch 3 O)mentioning
confidence: 96%